2020
DOI: 10.1038/s41598-020-72629-9
|View full text |Cite
|
Sign up to set email alerts
|

PM014 attenuates radiation-induced pulmonary fibrosis via regulating NF-kB and TGF-b1/NOX4 pathways

Abstract: Radiation therapy is the mainstay in the treatment of lung cancer, and lung fibrosis is a radiotherapy-related major side effect that can seriously reduce patient’s quality of life. Nevertheless, effective strategies for protecting against radiation therapy-induced fibrosis have not been developed. Hence, we investigated the radioprotective effects and the underlying mechanism of the standardized herbal extract PM014 on radiation-induced lung fibrosis. Ablative radiation dose of 75 Gy was focally delivered to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 48 publications
0
11
0
Order By: Relevance
“…We have previously shown that TGF-β is upregulated in a mouse model of fibrosis caused by SMG excretory duct ligation and that in vivo administration of TGF-β inhibitors reduces duct ligation-induced salivary gland fibrosis [ 97 ]. TGF-β inhibition also efficiently reduces IR-induced lung [ 98 , 99 ] and rectal [ 100 ] fibrosis in mouse models. Further investigation is needed on the relationship of TGF-β and fibrosis to IR-induced hyposalivation and whether this pathway plays a significant role in chronic salivary gland dysfunction in RT.…”
Section: Animal Models Provide Mechanistic Insight Into Radiation-mentioning
confidence: 99%
“…We have previously shown that TGF-β is upregulated in a mouse model of fibrosis caused by SMG excretory duct ligation and that in vivo administration of TGF-β inhibitors reduces duct ligation-induced salivary gland fibrosis [ 97 ]. TGF-β inhibition also efficiently reduces IR-induced lung [ 98 , 99 ] and rectal [ 100 ] fibrosis in mouse models. Further investigation is needed on the relationship of TGF-β and fibrosis to IR-induced hyposalivation and whether this pathway plays a significant role in chronic salivary gland dysfunction in RT.…”
Section: Animal Models Provide Mechanistic Insight Into Radiation-mentioning
confidence: 99%
“…Due to the uncontrolled release of TGF-β1 by a prolonged inflammatory state [ 198 ], pulmonary fibrosis is regarded as the main final fatal complication in PCS patients due to the uncontrolled release of TGF-β1 by a prolonged inflammatory state [ 198 ]. Therefore, TGF-β1 inhibitors like triptolide, azithromycin, and vitamin D could be effective in the attenuation of PCPF [ 199 ]. Of interest, pirfenidone, a TGF-β1 inhibitor that acts as an anti-fibrotic agent together with anti-inflammatory drugs, may reduce the risk of development of PCPF in COVID-19 survivors [ 200 ].…”
Section: Introductionmentioning
confidence: 99%
“…The underlying cellular and molecular mechanisms of radiation‐induced pro‐inflammatory and pro‐fibrotic signalling are being actively investigated in the lung, 13 liver, 14 and kidney 15,16 . Amongst these cytokines expressed after radiation are transforming growth factor‐β1 (TGF‐β1), C–C chemokine receptor type 2 (CCR2), and its associated ligands such as CCL2 17 . Chronic TGF‐β1 expression promotes fibroblast proliferation and myofibroblast differentiation, where these cells produce collagens and ECM proteins such as fibronectin (FN1) 18 .…”
Section: Introductionmentioning
confidence: 99%
“…15,16 Amongst these cytokines expressed after radiation are transforming growth factor-β1 (TGF-β1), C-C chemokine receptor type 2 (CCR2), and its associated ligands such as CCL2. 17 Chronic TGF-β1 expression promotes fibroblast proliferation and myofibroblast differentiation, where these cells produce collagens and ECM proteins such as fibronectin (FN1). 18 Additionally, CCR2-expressing immune cells are induced in irradiated pulmonary tissues 12 and colocalize to fibrotic areas.…”
Section: Introductionmentioning
confidence: 99%